2016
DOI: 10.21608/ejnf.2016.74876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chickpea Screenings by-Products as Untraditional Energy Source on Growth Performance and Digestibility of Growing Rabbits

Abstract: his work aimed to study the effects of partial and complete substitution of barley by chickpea screenings by-products (CSB) at levels 25, 50, 75 and 100% in rabbit diets on growth performance and nutrients digestibility of New Zealand White rabbits. Seventy five rabbits, five weeks old with an average body weight 786.73 g±32.02 were randomly divided into five groups. Each group included five replicates (three rabbits each). Results of growth trail revealed that rabbits fed 25% and 50% CSB achieved significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
(26 reference statements)
2
5
0
Order By: Relevance
“…In regard to kidneys function, rabbits fed diets included 30% LSBP and 15 or 30% CSBP had a significant decrease (P<0.05) in creatinine levels compared with 15% LSBP and the control group. Similar results were observed by Hassan et al (2016) who reported insignificant differences in globulin between rabbits fed diets contained chickpea screenings by-products at levels of 25, 50, 75 and 100% of barley compared to the control group, while rabbits fed 50% chickpea screenings by-product had higher (P<0.05) plasma total protein concentration than the control group. The present results disagreed with findings reported by Algam et al (2012) who demonstrated that 10% chickpea had no significant effect on plasma total protein of broiler chicks.…”
Section: Blood Plasma Parameterssupporting
confidence: 88%
See 4 more Smart Citations
“…In regard to kidneys function, rabbits fed diets included 30% LSBP and 15 or 30% CSBP had a significant decrease (P<0.05) in creatinine levels compared with 15% LSBP and the control group. Similar results were observed by Hassan et al (2016) who reported insignificant differences in globulin between rabbits fed diets contained chickpea screenings by-products at levels of 25, 50, 75 and 100% of barley compared to the control group, while rabbits fed 50% chickpea screenings by-product had higher (P<0.05) plasma total protein concentration than the control group. The present results disagreed with findings reported by Algam et al (2012) who demonstrated that 10% chickpea had no significant effect on plasma total protein of broiler chicks.…”
Section: Blood Plasma Parameterssupporting
confidence: 88%
“…However, it is clearly noticed insignificant differences in DCP%, TDN% and DE Kcal/kg among the control group and the other tested groups. On the contrary, Hassan et al, (2016) demonstrated that rabbits group fed 25 or 50% chickpea screenings by-products recorded significantly (P<0.05) higher digestibilities of DM, OM, CP, CF, EE and NFE compared with the other tested levels of 0, 75 and 100% chickpea screenings by-products. As well the digestibility and biological value of chickpea nutrients are high for poultry (Brenes et al, 2008 andNalle, 2009).…”
Section: Nutrients Digestibility and Nutritive Valuesmentioning
confidence: 77%
See 3 more Smart Citations